Rehabilitation of Patients with Paraplegia from Spinal Cord Injury: A Review - Al Hasan, Suzon; Alam, Zahangir; Hakim, Maliha; Shakoor, Md Abdus; Salek, AKM; Khan, Md Moniruzzaman; Ahmed, Syed Mozaffar; Rashid, Md Abdur; Islam, Monirul; Uddin, Md Taslim; et al. (Journal of Chittagong Medical College Teachers’ Association, 2010)
DOI: 10.3329/jcmcta.v20i1.4937 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):53-57